Establishment of a New Abdominal Aortic Aneurysm Model in Rats by a Retroperitoneal Approach - Zhu, Jun-Xing; Tang, Quan-Qiao; Zhou, Can; Shi, Xing-Chi; Yi, Si-Yi; Yang, Ying (Frontiers in Cardiovascular Medicine, 2022)
Background Constructing an ideal model of abdominal aortic aneurysm (AAA) is of great significance to elucidate its complex pathogenesis. Therefore, we introduce a new and simple method to simulate human AAA and construct a rat AAA model through a retroperitoneal approach. Methods Forty healthy adult Sprague Dawley (SD) rats were randomly divided into a control group, elastase + calcium chloride group (PPE+CaCl2), elastase group (PPE), and elastase + beta aminopropionitrile group (PPE+BAPN) according to a male-female ratio of 1:1, with 10 rats in each group. A retroperitoneal approach was used to free the infrarenal abdominal aorta in all four groups. In the PPE + CaCl2 group, 0.1 ml of elastase (approximately 5 U) was perfused into the arterial cavity for 20 min, and 1.0 mol/L calcium chloride was infiltrated out of the arterial cavity for 10 min. In the PPE group, 0.1 mL of elastase (approximately 5U) was perfused into the arterial cavity for 20 min, and normal saline was infiltrated out of arterial cavity for 10 min; the PPE + BAPN group combined with 0.3% BAPN drinking water/day on the basis of PPE group; the control group was treated with saline instead of elastase and calcium chloride. Abdominal aortic specimens were collected after 4 weeks of feeding. The diagnostic criteria of AAA were 50% dilation of the abdominal aorta or rupture of the aneurysm at 4 weeks after the operation. Histopathology, immunohistochemistry, quantitative PCR (qPCR), western blotting assay, gelatine zymogram, and other methods were used. Results The operation time of the four groups was controlled at approximately 40 min, and the success rate of the operation was 100%. Survival rate: Control Group (100%) = PPE Group (100%) > PPE + CaCl2 Group (90%) > PPE + BAPN Group (40%); Aneurysm formation rate: PPE + BAPN Group (100%) > PPE + CaCl2 Group (80%) > PPE Group (60%) > Control Group (0%); Aneurysm rupture rate: PPE + BAPN group (60%) > PPE + CaCl2 group (12.5%) > PPE group (0%);Inflammatory cells (macrophages, T cells, B cells, dendritic cells) infiltrated in different degrees in the PPE + CaCl2, PPE and PPE + BAPN groups. Vascular thickness, elastic fiber content, collagen fiber content, and vascular smooth muscle cell content in the PPE + CaCl2 group and PPE + BNPA group were significantly lower than those in Control group (P < 0.05). The content of elastic fibers and vascular smooth muscle cells in the PPE group were significantly lower than that in Control group (P < 0.05). The expression and activity of matrix metalloproteinase 2 (MMP2) and MMP9 in the PPE + CaCl2 group, PPE group, and PPE + BNPA group were significantly higher than those in the control group (P < 0.05). Conclusions A new, simple, and reproducible rat AAA model can be constructed by a retroperitoneal approach. The pathological features of the three models are effective simulation of human AAA inflammatory cell infiltration, protease activity enhancement, and extracellular matrix destruction. The PPE+ CaCl2 model has the advantages of a high survival rate, high aneurysm formation rate, good stability, and reproducibility. It is an ideal animal model for studying the pathogenesis of AAA. The PPE + BAPN model can simulate the characteristics of spontaneous rupture of aneurysms. It is an ideal animal model to study the mechanism of AAA rupture.